Rearing practices identified as risk factors for ostreid herpesvirus 1 (OsHV-1) infection in Pacific oyster Crassostrea gigas spat - Normand, Julien; Blin, Jean-louis; Jouaux, Aude (Diseases of Aquatic Organisms, 2014)
Early detection of Pacific oyster spat infected with ostreid herpesvirus 1 (OsHV-1) could prevent introduction of OsHV-1-infected individuals into farming areas or onshore rearing facilities, thus reducing the risk of infection of naïve oysters in such production systems. Experiments were conducted on several hundred oyster spat provided by producers in order to examine whether early rearing practices could be considered as potential risk factors for (1) OsHV-1 infection as detected by molecular methods and (2) spat mortality experimentally induced through thermal challenge. Spat groups collected on oyster beds and hatchery spat reared in growout areas during summer exhibited higher viral DNA contamination and mortalities during the trial than spat kept in onshore rearing facilities. Quantification of viral DNA before and during the trial showed that infection prevalence and intensity changed over time and revealed latent infection initially unsuspected in 3 of 10 groups. Thermal challenge induced a clear increase in the probability of detecting infected individuals, particularly for groups exhibiting significant prevalence of OsHV-1-contaminated spat prior to the challenge. The use of detection methods are discussed in relation to early rearing practices and disease control strategies. La détection précoce des lots de naissain d'huître creuse porteurs du virus OsHV-1 pourrait permettre d'éviter leur introduction dans des zones ou des installations d'élevage (en mer, ou à terre) jusque là épargnées par les mortalités de naissain. L'étude rapportée ici s'intéressait à l'effet des pratiques d'élevage "précoces" sur : 1) la probabilité de détection de l'OsHV-1 par les méthodes moléculaires de diagnostic et 2) la probabilité de mortalité révélée au moyen d'un protocole expérimental de conditionnement zootechnique du naissain. Les résultats montrent que les lots de naissain gardés isolés dans des structures d'élevage à terre présentent une probabilité de détection de l'OsHV-1 moindre que les lots issus de captage ...